P60 The creation of an autoimmune hepatitis register and a nurse-led service: a worthy lock-down pastime. (28th September 2020) - Orange, Dawn; Turner, Lucy; Maher, Laura; Pratt, Anthony; Millson, Charles; Arikichenin, Olithselvan; Driver, Robert
Abstract : Introduction: Autoimmune Hepatitis (AIH) is a relapsing chronic inflammatory condition 1 that waxes and wanes irrespective of outpatient clinic scheduling. York Teaching Hospital NHS Foundation Trust (YTHT) covers a wide geographical area. 2 The COVID-19 pandemic has demonstrated that not all patients require regular clinical review in person. Aim: To update the clinical registry of AIH patients within YTHT, ensuring appropriate monitoring during Covid-19, and prompt review for those requiring it. Methods: An IT-based search identified individuals' with a diagnosis of AIH within YTHT. An electronic note review established demographic details, risk factors for co-existing liver disease, severity of AIH, disease treatment, and current blood results. Results: 128 patients were identified, 81% of whom were female. The average age was 68 years (range 17–88). 51% were local to York Hospital and 34% closer to Scarborough Hospital, as demonstrated in figure 1 . The remainder travel to their closest hub. 55% of the cohort had an elevated ALT suggesting ongoing disease activity (arguably ALT >31UI/L in males and ALT >21 UI/L in females). 62% were taking significant immunosuppression; Azathioprine 32%, Mycophenolate Mofetil 14.4%, Tacrolimus 9.6% and Prednisolone >20 mg/day 6.4%. Discussion: The COVID-19 pandemic has demonstrated the need to identify and offer timely follow-up for our most unwell patients, allowing those with a stable condition to safely shield. Virtual monitoring of patients is important to identify asymptomatic flares. We advocate incorporating nurse-led monitoring of such patients, in combination with patient initiated follow-up for those with symptomatic disease. References: Heneghan MA, Yeoman AD, Verma S, Smith AD, Longhi MS. Autoimmune hepatitis. Lancet . 2013;382 (9902):1433–1444. www.yorkhospitals.nhs.uk/about-us/